2021
DOI: 10.1155/2021/8836818
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Sigma‐1 Receptor Protects against Cardiac Fibrosis by Alleviating IRE1 Pathway and Autophagy Impairment

Abstract: Sigma-1 receptor (Sig1R), a chaperone in the endoplasmic reticulum (ER) membrane, has been implicated in cardiac hypertrophy; however, its role in cardiac fibroblast activation has not been established. This study investigated the possible association between Sig1R and this activation by subjecting mice to sham, transverse aortic constriction (TAC), and TAC plus fluvoxamine (an agonist of Sig1R) treatments. Cardiac function and fibrosis were evaluated four weeks later by echocardiography and histological stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Defective autophagy results in development of heart failure (37), however the role of autophagy in CFs is less known. Recent evidence indicated that autophagic f l u x w a s i m p a i r e d i n a c t i v a t e d C F s a n d f i b r o t i c hearts (38). Another study found that autophagy enhanced the activation of CFs and exerted a profibrotic role (39).…”
Section: Discussionmentioning
confidence: 99%
“…Defective autophagy results in development of heart failure (37), however the role of autophagy in CFs is less known. Recent evidence indicated that autophagic f l u x w a s i m p a i r e d i n a c t i v a t e d C F s a n d f i b r o t i c hearts (38). Another study found that autophagy enhanced the activation of CFs and exerted a profibrotic role (39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ER-Golgi is another important way to produce DMVs independent of the autophagy pathway. There is substantial evidence that CoVs induce membrane rearrangement by hijacking the host cell ERAD machinery ( Miller et al, 2020 ; Qu et al, 2021 ). NSPs regulate ER and Golgi apparatus rearrangement to form DMVs directly from the ER ( Gassen et al, 2019 ).…”
Section: Coronaviruses Hijack Autophagy Initiation and Erad Machinery...mentioning
confidence: 99%
“…Autophagy dysregulation is known as a key component of several neurodegenerative diseases including Alzheimer’s disease [ 47 ] and in recent years the sigma-1 receptor has been shown to be a target that can directly and indirectly affect autophagy as well as other cellular mechanisms that could be involved in neurodegeneration [ 48 ]. Recent research has shown that sigma-1 receptor stimulation using fluvoxamine activates autophagy and protects against cardiac fibrosis by inhibiting the IRE1 pathway [ 49 ].…”
Section: Sigma-1 Receptor Activation and Autophagymentioning
confidence: 99%